Read in the everyday culture. Everyday reading as a common modern modification of reading. Problem setting - J. P. Melentjeva (Библиосфера)
The place of reading phenomenon in the everyday culture is discussed. The idea of an «ordinary reading» as a new emerging modification, its features and the danger of its spreading as the main one are formulated.